The Abstract Task Graph - Bakshi, Amol B; Prasanna, Viktor K (Architecture-Independent Programming for Wireless Sensor Networks, 2007)
This chapter contains sections titled: Target Applications and Architectures Key Concepts Syntax Semantics Programming Idioms Future Work